SGLT1/2 as the potential biomarkers of renal damage under Apoe−/− and chronic stress via the BP neural network model and support vector machine - Hu, Gai-feng; Wang, Xiang; Meng, Ling-bing; Li, Jian-yi; Xu, Hong-xuan; Wu, Di-shan; Shan, Meng-jie; Chen, Yu-hui; Xu, Jia-pei; Gong, Tao; Chen, Zuoguan; Li, Yong-jun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Chronic stress (CS) could produce negative emotions. The molecular mechanism of SGLT1 and SGLT2 on kidney injury caused by chronic stress combined with atherosclerosis remains unclear. Methods: Sixty C57BL/6J mice were randomly divided into four groups, including control group (CON, n=15), control diet + chronic stress (CON+CS, n=15), high fat diet + Apoe-/- (HF+Apoe-/-, n=15), high fat diet + Apoe-/- + chronic stress (HF+Apoe-/-+CS, n=15). Elevated plus maze and open field test assay were performed to exam the effect of chronic stress. The expression of SGLT1 and SGLT2 in kidney was detected. Support vector machine (SVM) and Back Propagation (BP)-neural network model were constructed to explore the predictive value of expression of SGLT1/2 on the renal pathological changes. The receiver operator characteristic (ROC) curve analysis was used. Results: Chronic stress model and atherosclerosis model were constructed successfully. Edema, broken reticular fiber, increased glycogen in kidney would be obvious in HF+Apoe-/-+CS group. Compared with the CON group, expression of SGLT1/2 in kidney were up-regulated in the HF+Apoe-/-+CS group (P<0.05). There existed positive correlations among edema, glycogen, reticular fiber, expression of SGLT1/2 in kidney. There were higher sensitivity and specificity of diagnosis of SGLT1/2 for edema, reticular fiber, glycogen in kidney. The result of SVM and BP-neural network model showed better predictive value of SGLT1 and SGLT2 for edema, glycogen in kidney. Conclusion: In conclusion, SGLT1/2 might be potential biomarkers the renal damage under Apoe-/- and chronic stress, which provided a potential research direction for future, related explorations into this mechanism.